INDIKASI PREDATORY PRICING PADA PRAKTEK FLASH SALE PELAKU USAHA E-COMMERCE DALAM PERSPEKTIF HUKUM PERSAINGAN USAHA - Fitri Fitri; Sri Jaya Lesmana (SUPREMASI HUKUM, 2021)
The ease of business transactions offered by e-commerce services makes many companies compete with each other to offer attractive promos to consumers or the public so that they are interested in making transactions on their e-commerce services, one of the promos offered is by providing discounts or discounts in certain time or better known as flash sale. However, in practice, flash sales are often accompanied by very large discounts on a product, even reaching the price of Rp. 99, - (ninety nine rupiah). The price offered is very different from the market price that should be, this gives an indication of predatory pricing or selling at a loss carried out by e-commerce business actors. The problem that will be raised by the author is how the flash sale method is carried out by e-commerce business actors and how is predatory pricing law enforcement based on Law Number 5 of 1999 concerning Monopolistic Practices and Unfair Business Competition. The flash sale practice carried out by e-commerce business actors does not violate the provisions of Article 20 of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition if the price offered is below the production price with the aim of expelling business competitors in the market the same time, and in the future raise prices as much as possible in order to cover losses and gain profits where the price increase causes losses for consumers. Keywords: Flash Sale; Predatory Pricing; Business Competition.